Experimental evidence for an attractive p-phi interaction - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Kroesen, Martin; Nath, Abhishek; et al. (Physical review letters, 2021)
This Letter presents the first experimental evidence of the attractive strong interaction between a proton and a ϕ meson. The result is obtained from two-particle correlations of combined p−ϕ⊕ ¯p−ϕ pairs measured in high-multiplicity pp collisions at √s=13  TeV by the ALICE Collaboration. The spin-averaged scattering length and effective range of the p−ϕ interaction are extracted from the fully corrected correlation function employing the Lednický-Lyuboshits approach. In particular, the imaginary part of the scattering length vanishes within uncertainties, indicating that inelastic processes do not play a prominent role for the p−ϕ interaction. These data demonstrate that the interaction is dominated by elastic p−ϕ scattering. Furthermore, an analysis employing phenomenological Gaussian- and Yukawa-type potentials is conducted. Under the assumption of the latter, the N−ϕ coupling constant is found to be gN−ϕ=0.14±0.03(stat)±0.02(syst). This work provides valuable experimental input to accomplish a self-consistent description of the N−ϕ interaction, which is particularly relevant for the more fundamental studies on partial restoration of chiral symmetry in nuclear medium.
*ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, A. Berdnikova, L. Bergmann, M.C. Danisch, V.J.G. Feuillard, P. Glaessel, J. Kim, M. Kim, M. Kroesen, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, M.A. Völkl, B. Windelband [und 1008 weitere Personen]
Gesehen am 16.12.2021
Im Titel ist "phi" als griechischer Buchstabe dargestellt